The energy sparing effect of guanidinoacetic acid alone or in conjunction with exogenous enzymes in broiler diets - Jansen van Rensburg, Christine (University of Pretoria, 2021)
Dissertation (MSc (Agric) Animal Science: Animal Nutrition)--University of Pretoria, 2021.